Precision oncology - Guideline of the Austrian, German and Swiss Societies for hematology and medical oncology - Rieke, Damian; Bitzer, Michael; Bleckmann, Annalen; Desuki, Alexander; Ernst, Thomas; Esposito, Irene; Gerger, Armin; Glimm, Hanno; Horak, Peter; Hübschmann, Daniel; Illert, Anna Lena; Kunzmann, Volker; et al. (European journal of cancer, 2025)
Precision oncology is a multi-step process including patient selection, tumor profiling, molecular tumor board discussion and personalized cancer management. So far, it remains largely unstandardized. The implementation of precision oncology can be beneficial for patients but implementation differs widely between tumor types and local practices. A working group was established by the Austrian, German and Swiss societies for Hematology and Medical Oncology to establish an expert consensus on evidence-based standards and implementation of precision oncology. Herein, we present a summary of this guideline. The full documents are available at www.onkopedia-guidelines.info